Competing visions: security of tenure and the welfarisation of English social housing. Issue 8 (17th November 2017) - Fitzpatrick, Suzanne; Watts, Beth
Abstract: Recent legislation ending security of tenure for new council tenants in England may be considered emblematic of a US-style vision of social housing as a temporary welfare service, reserved only for the very poorest. But there is resistance amongst social landlords, many of whom remain committed to providing 'homes for life'. Moreover, austerity-driven cuts mean that benefit-dependent households are increasingly refused social tenancies on grounds of affordability. The stage is therefore set for a battle over who and what English social housing is for. Drawing on large-scale qualitative research, this paper interrogates the implications of the mandatory extension of fixed-term tenancies (FTTs) by considering landlord and tenant experiences of the discretionary FTT regime in place since 2012. We conclude that the meagre likely benefits of FTTs, in terms of marginally increased tenancy turnover, are heavily outweighed by the detrimental impacts on tenants' ontological security and landlords' administrative burden.